A concept paper on compliance with NADOPOD regulation and guideline Vis-À-Vis the Occupational Safety and Health Act 1994 among technology-based SME in Northern State of Peninsular Malaysia - Dayang Hasliza, Muhd Yusuf; Azuddin, Bahari, Lt. Kol. (B); Wan Sallha, Yusoff (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.